Case Report: Primary endodermal sinus tumor on the abdominal wall near the right liver: a diagnostic pitfall - Chen, Shuo; Chen, Feng; Xu, Xiao (Frontiers in Oncology, 2023)
Endodermal sinus tumors are rare, especially extragonadal endodermal sinus tumors, which often occur in the midline of the brain, neck, chest and abdomen.Female, 37 years old, with a mass on the right edge of the liver. Color Doppler ultrasound, computed tomography and magnetic resonance imaging examinations were performed before operation. Given these results and the elevation of alpha-fetoprotein, the diagnosis of hepatocellular carcinoma was made. Postoperative pathological examination indicated an endodermal sinus tumor on the abdominal wall near the right liver. The causes of misdiagnosis were analyzed, and the related literature was reviewed.Primary endodermal sinus tumors on the abdominal wall near the right liver are easily misdiagnosed as hepatocellular carcinoma due to liver compression and elevated alpha-fetoprotein. The key point of differentiation is the wide basal connection between the tumor and the abdominal wall near the liver. In addition, the enhancement mode of endodermal sinus tumors is different from the enhancement pattern of hepatocellular carcinoma.